2017
DOI: 10.4317/jced.53570
|View full text |Cite
|
Sign up to set email alerts
|

Bonding to silicate ceramics: Conventional technique compared with a simplified technique

Abstract: BackgroundSilicate ceramic bonding is carried out by acid-etching with hydrofluoric acid (HF) followed by an application of silane. By replacing HF with ammonium polyfluoride, contained in the same flask as the silane, the number of steps in this clinical procedure, can be reduced, while maintaining bond strength values, and reducing toxicity. A shear bond test was performed to compare the conventional and the simplified surface treatment techniques.Material and Methods Twenty ceramic samples were fabricated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
29
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 5 publications
(5 reference statements)
9
29
1
1
Order By: Relevance
“…We failed to reject the null hypothesis. These findings are in agreement with previous studies that found that the use of MEP for surface pre-treatment of glass ceramic blocks provides adequate bond strength that is equivalent to the conventional technique [13][14][15]. On the contrary, other studies reported that shear bond strength of resin cement to CAD/CAM glass ceramics when treated with MEP is significantly lower when compared to pre-treatment with hydrofluoric acid.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We failed to reject the null hypothesis. These findings are in agreement with previous studies that found that the use of MEP for surface pre-treatment of glass ceramic blocks provides adequate bond strength that is equivalent to the conventional technique [13][14][15]. On the contrary, other studies reported that shear bond strength of resin cement to CAD/CAM glass ceramics when treated with MEP is significantly lower when compared to pre-treatment with hydrofluoric acid.…”
Section: Discussionsupporting
confidence: 92%
“…This new Self-etching primer (Monobond etch and prime, Ivoclar Vivadent, Schaan, Liechtenstein) simplifies the bonding procedure by decreasing the number of steps as well as saving chairside time. In vitro studies showed that Monobond etch and prime had comparable bond strength to the conventional bonding method [13,14]. In a short clinical study, the use of MEP offered a simplified alternative approach with good clinical results [13].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the effective bonding may be attributed to the chemical affinity between silica in lithium disilicate and ammonium trifluoride in Monobond. (45,64) These finding were supported by many researchers, (65,66) who recorded morphological observations of silica glass matrix in lithium disilicate . The displaced glass matrix due to the polyfluoride component of Monobond, becomes incorporated into the adhesive bond with the resin cement.…”
Section: Discussionsupporting
confidence: 60%
“…(41,42) Universal adhesives represent the latest generation of dental adhesives that failed to prove their manufacturers' claims that they can be used as bondng agents on ceramic surfaces after HF surface treatment. (43)(44)(45) Recently, a novel single bottle selfetching ceramic primer, (Monobond® etch & prime), (Ivoclar Vivadent; Schaan, Liechtenstein), was introduced. It has the advantage of easier handling, less technique sensitivity and less time consumption (Single step).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation